O saber experiencial na formação inicial de professores a partir das atividades de iniciação à docência no subprojeto de química do PIBID da Unesp de Araraquara - Silva, Camila Silveira da [UNESP]; Maruyama, José Antonio [UNESP]; Oliveira, Luiz Antonio Andrade de [UNESP]; Oliveira, Olga Maria Mascarenhas de Faria [UNESP] (My University, 2012)
Experiential Knowledge of Initial Teacher Training and from the Activities Started Teaching in Chemistry Subproject PIBID Unesp of the Araraquara. This paper discusses the contribution of the activities of the subproject PIBID the Institute of Chemistry of Araraquara UNESP for the training of undergraduates (initiation to teaching scholarship), basing our approach on the ideas of Maurice Tardif (2012) on teacher knowledge, focusing we mainly experiential knowing. We analyzed data from the reports of the fellows from initiation to teaching and a questionnaire in one of the team meetings of the subproject. Both the report and the stock market in the questionnaire and analyzed for the preparation of this text, the focus is on reports and answers about the contribution of PIBID for the training of undergraduates in chemistry subproject participants.

O presente trabalho aborda a contribuição das atividades do subprojeto do PIBID do Instituto de Química da Unesp de Araraquara para a formação dos licenciandos (bolsistas de iniciação à docência), fundamentando nossa abordagem nas ideias de Maurice Tardif (2012) sobre os saberes docentes e focando-nos principalmente no saber experiencial. Analisamos dados obtidos a partir dos relatórios dos bolsistas de iniciação à docência e de um questionário aplicado em uma das reuniões da equipe do subprojeto. Tanto no relatório da bolsa quanto no questionário aplicado e analisado para a elaboração do presente texto, o foco está nos relatos e nas respostas sobre a contribuição do PIBID para a formação profissional dos licenciandos em química participantes do subprojeto.
Keywords: PIBID; química; Saber experiencial